Meningkatkan Hasil Belajar Passing dan Stopping Permainan Futsal Melalui Model Pembelajaran Problem Based Learning - Trimai Saputra Rizky; Zulkifli Zulkifli (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to improve the learning outcomes of passing and stopping futsal games through problem-based learning. This research is in the nature of PTK (Class Action Research) with a total of 24 students in class X Agrinak consisting of 14 boys and 10 girls. This research was conducted for two actions (cycles). Each action includes planning, implementation, observation and reflection. Data collection techniques through learning achievement tests. Where in the skills of students during the first cycle there were no students who achieved a completeness score. This means that the results of the first cycle have not reached the classical completeness score of 80% of the number of students. In the second cycle it shows that the students' ability to perform futsal passing and stopping movements is very good compared to cycle I with a completeness score of 100%, meaning this has exceeded the classical completeness score of 80% of the number of students. The passing skills of futsal students during the first cycle of action were not completed by students. In cycle II there was an increase with the acquisition of classical completeness scores as many as 24 students completed or by 100% an increase of 100%.